Multidimensionality of behavioural engagement: Empirical support and implications. (2016) - Hospel, Virginie; Galand, Benoît; Janosz, Michel
Highlights: The findings support the presence of distinct dimensions of behavioural engagement. Five dimensions are distinguished (participation, disruptive behaviours, etc.). They are facets of a same common construct, namely behavioural engagement. Implications of using a global measure vs. specific dimensions are discussed. Abstract: Behavioural engagement refers to a large range of student behaviours, differing from one study to another. What are the advantages and disadvantages of using a global measure or specific behaviours? The aim of the present study was to test the multidimensionality of the construct of behavioural engagement (presence of distinct dimensions and relevance of grouping them). Five dimensions were distinguished: participation, following instructions, withdrawal, disruptive behaviour and absenteeism (explanatory factorial analyses, Sample 1). Confirmatory factorial analyses supported the grouping of these dimensions in a common construct (Sample 2). The links between correlates and a global measure of behavioural engagement or specific dimensions were generally consistent. The global measure hid differences in relations between dimensions and some correlates. Taking the multidimensionality of behavioural engagement into account appears crucial.